2014
DOI: 10.1007/s12639-014-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of Enterobius vermicularis among appendicitis patients in Gaza strip, Palestine

Abstract: Enterobius vermicularis is one of the most common intestinal parasite in human. The main objective of this study is to determine the role of E. vermicularis in appendicitis through histopathological examination. A cross sectional study included 200 patients who had appendectomy from three hospitals in Gaza strip. The inflamed appendix was the cause of attending the hospital. Histopathological examination for each appendix was carried out. A questionnaire was designed (interview with patients who underwent appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The results were comparable to those found (30), which showed that the infection with the parasite E. vermicularis by 11.6%. This is almost consistent with what was stated (31)(32)(33)(34)(35)(36)(37)(38)(39), which confirmed that the most parasitic etiology of appendicitis is E. vermicularis where the adult parasite is isolated as well as its eggs from the inflamed appendix that has been surgically removed (40)(41)(42). The results are also lower than the results (32), Where 18.2% of those who suffer from appendicitis recorded the presence of the parasite E. vermicularis, also pointed to the presence of E. vermicularis in inflammatory appendages more than healthy appendages.…”
Section: Discussionsupporting
confidence: 93%
“…The results were comparable to those found (30), which showed that the infection with the parasite E. vermicularis by 11.6%. This is almost consistent with what was stated (31)(32)(33)(34)(35)(36)(37)(38)(39), which confirmed that the most parasitic etiology of appendicitis is E. vermicularis where the adult parasite is isolated as well as its eggs from the inflamed appendix that has been surgically removed (40)(41)(42). The results are also lower than the results (32), Where 18.2% of those who suffer from appendicitis recorded the presence of the parasite E. vermicularis, also pointed to the presence of E. vermicularis in inflammatory appendages more than healthy appendages.…”
Section: Discussionsupporting
confidence: 93%
“…The disease typically has a benign evolution with rare complications, and anthelmintic therapies are effective in the majority of cases (Cook, 1994;Georgiev, 2001;Botero and Restrepo, 2012). Ectopic locations are uncommon, but pinworms can occasionally be detected in the appendix (Tapia and Muñoz, 2011;Levens et al, 2014;Hamdona et al, 2016;Lala and Upadhyay, 2016), kidney, liver, lung, urinary tract, female genital tract (Cook, 1994;Das et al, 2001;Craggs et al, 2009;Powell et al, 2013;Kashyap et al, 2014;Ngui et al, 2014;Pigac et al, 2017), mesenteric lymph node (Zafar et al, 2018) and caecal polyp (Elsaid et al, 2014), which are all potential reservoirs of this parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of enterobiasis involving the appendix are diagnosed by finding adult worms in the lumen. 2,3 The presence of the parasite in the wall of the appendix has also been reported. 4,5 However, the invasive potential of E vermicularis has not been conclusively proved, and deserves future study.…”
Section: Discussionmentioning
confidence: 94%